The Legal System for the Management of Household and Similar Waste as a Mechanism for Achieving a Circular Economy in Algerian Legislation - Belazzoug, Bilal; Benamier, Djameleddine (Journal of Legal Studies and Researches, 2021)
Household and similar wastes are considered the most common waste in the world, which has prompted countries to work hard to protect the environment from them on the one hand and in return to constantly search to recycle and manage them sustainably. The importance of renewable energies. at the international level also increased after its qualitative support for the national economy of developed countries by devoting the so-called circular economy.